(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Forensic Anthropometry is an important tool in establishing the identity of mortal remains. This study aimed to investigate various dimensions of the mandible for sex determination in forensic and anthropological research. 50 normal mandibles from individuals between 20-50 years old were collected and measured using vernier calipers, mandibulometer, and measuring tape. The study found that mandible dimensions can accurately determine sex in highly decomposed or mutilated bodies. The Symphyseal Height, Body Height, Length of the Lower Jaw, Minimum Breadth of Ramus, Maximum Breadth of Ramus, Bigonial Breadth, Bicondylar Width, and Bimental Width were all found to be larger in males than females, with statistically significant differences observed for each of these parameters. The study found that Body Thickness and Body Length were not significantly different between males and females.